The long-awaited study of dental medicine in the Faculty of Medicine at the University of Maribor (the MF UM) is to begin in the 2021/22 academic year / V akademskem letu 2021/22 se na Medicinski fakulteti Univerze v Mariboru začne dolgo pričakovani študi - Mičetić-Turk, Dušanka (Acta Medico-Biotechnica, 2021)
The great Chinese philosopher Confucius once said, “When you make the first step, you have already reached the goal.” The incentive to make the first step in the direction of organizing the study of dental medicine in the Faculty of Medicine at the University of Maribor (MF UM) came from the dental service of the Health Centre Dr. Adolf Drolc in 2016. At the MF UM, we immediately recognized the incentive as a great opportunity for sustainable development in the region; not only in the sense of educating doctors of dental medicine, but also as an opportunity to develop new, interdisciplinary cooperation between the various faculties of the University of Maribor in the fields of dental medicine, which include studies of new materials, nanoparticles, microbiology, genetics, biochemistry, and bioinformatics, among others. Thus, the painstaking establishment of the uniform Master's Program in Dental Medicine was initiated and concluded on January 09, 2020 by order of the Slovenian Quality Assurance Agency for Higher Education on programme accreditation ...